Some universal results for exchange spring magnets and applications to DyFe2/YFe2 superlattices - Bowden, G; Daniell, G; Gordeev, SN; Beaujour, J; de Groot, P; Rainford, B; Ward, R; Wells, MR (2002)
We present some universal results for exchange springs in multilayer systems with alternating hard and soft layers. In particular, the reduced magnetisation 〈cosθ〉, for both symmetric exchange springs (0→φ→0) and 180° exchange springs (0→π), is given in terms of elliptic functions. The result for the symmetric exchange spring is found to be in good accord with experimental results on MBE grown DyFe2/YFe2 multilayers. © 2002 Elsevier Science B.V. All rights reserved.